Dampak investasi sektor pertambangan hulu migas terhadap nilai tambah bruto penyerapan tenaga kerja dan import content di Indonesia - Nazorry Effendy (Lembaga Pengembangan Manajemen dan Publikasi Imperium, 2019)
This paper aims to provide an important point of view on the impact of investment in the upstream oil and gas mining sector on gross added value (business surplus, wages, depreciation, and indirect taxes), transportation of labor, and imports. Research data were collected through external sources and synthesized with critical analysis to explain the linkages of the Indonesian mining investment sector. In general, the results of the study show that investment in the upstream oil and gas mining sector has a positive impact on the gross added value of its components (business surplus, wages, and revenues, depreciation, indirect taxes), employment search, and content import. Implications and suggestions are explained in this paper.